The Relationship Between Self-Determination and Metacognition of Junior High School Students in Mathematics Learning Based on Gender - Muhammad, Iryana; Jupri, Al; Dahlan, Jarnawi Afgani; Turmudi, Turmudi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2024)
This research is a quasi-experimental research that aims to determine the relationship between metacognitive abilities and students' self-determination in mathematics subjects based on gender. The population in this study were all students in class VIII of Lhokseumawe City Islamic Middle School with a sample of 27 students. Data was obtained from the results of a self-determination ability questionnaire and a metacognitive questionnaire which was then carried out by Spearman correlation testing. The results of the correlation between metacognitive abilities and self-termination obtained a significance value which shows that there is a correlation between metacognitive abilities and students' self-determination in learning mathematics. For the correlation between metacognitive abilities and students' self-determination in learning mathematics in terms of gender using the Spearman correlation test for each gender, correlation values ​​were obtained for males (r_1) and females (r_2). Based on the results of the difference test between the means of two independent groups, a z-count value was obtained which shows that there is no difference in correlation between the two groups.